Advantages and challenges in implementing digital transformation in some high schools in the Mekong Delta - Lam Thi Thanh Vo; Vuong Van Ly; Trang Bao Nguyen; Hang Thi Thuy Nguyen; Phuong Thi Ha Tran; Quang Minh Dinh (Kasetsart Journal of Social Sciences, 2026)
The rapid advancement of technology has significantly accelerated the digital transformation in Vietnamese education, introducing innovative teaching methods and yielding promising results. This study involved surveying 45 high school teachers from three different provinces and cities in the Mekong Delta: Can Tho, Soc Trang, and Ca Mau. The aim was to evaluate their perspectives on the benefits and challenges of digital transformation in educational institutions. The findings indicate that while digital transformation offers several advantages—such as enhancing student engagement, streamlining document preparation, and improving student management—teachers still face notable challenges, particularly concerning inadequate infrastructure and a lack of reference materials. Further research involving a broader participant base and a more extensive exploration of the root causes is recommended to gain a deeper understanding of these issues.